Unes justes al pont dels Serrans de València en 1320. - RODRIGO LIZONDO, MATEU (Scripta)
The present article deals with one of the oldest jousts on record in Spain, which took place in València under Jaume II. Gonçalbo Ferrandis, assistant to the governor general of the kingdom of València, agreed with "the wild knight" Francesc de Santaeugènia to fight against him on horseback on 26 March 1320. Francesc de Santaeugènia was well known for his fondness for such engagements, and was expected to fight against Gonçalbo Ferrandis, who would engage in the joust equipped with chain mail, padded doublet, and spear. The armed encounter would take place at the Serrans bridge, where both jousters would try to prevent the other from crossing to the other side. The judge of the field was Rodrigo Llançol, the son of a knight. Santaeugènia did not appear, which led Ferrandis to file a suit. The proceedings have not been preserved in their entirety.